The Effectiveness Of Non Formal Education Programs By The Komunitas Sahabat Difabel (KSD) Semarang City In Empowering People With Disabilities - Kevina Lena Faustina (Eduvest - Journal of Universal Studies, 2024)
This research focuses on the empowerment of Komunitas Sahabat Difabel (KSD) Semarang City through non formal education programs. Komunitas Sahabat Difabel (KSD) offers various trainings such as sewing, hydroponic farming, and self-development. The program is designed to improve the practical, financial, and social skills of people with disabilities to reduce the social isolation and stigma they often face. The research method used is qualitative with a descriptive approach, including direct observation, in-depth interviews, and documentation. The results showed that the KSD program succeeded in improving participants' skills and confidence in facing various challenges, while this program can make changes in community perceptions. Therefore, this study emphasizes the importance of continuous support and comprehensive evaluation to ensure the effectiveness and sustainability of non formal education programs for people with disabilities in KSD Semarang City.